STREET DESIGN AND WOMEN’S SAFETY PERCEPTION - Abdul Rashid, Suhaila; Wahab, Mohammad Hussaini; Wan Mohd Rani, Wan Nurul Mardiah (PLANNING MALAYSIA, 2017)
Urbanization is a process that creates many opportunities as well as threats. It is a process that will keep on continuing as population rate, migration, economic and social pattern are changing. Along with urbanization, demand for sustainable development and public space is crucial. Streets are important public space in a city. It is a network for many kind of activities. Design of streets affects the way people use it as well as their perception on safety. As a public space, safety is an important factor to consider. A safe public space will create a liveable environment. Feeling safe is important for human being due to the fact the built environment does affect our perception. Gender plays a role in safety perception where women perceive their environment differently. This study focuses on the importance of street as public space in contributing towards safety perception. In order to evaluate the phenomenon, a mixed method approach was adopted. Four streets in the city centre which are important public space with trading activities, connected to educational institution, offices and other economic activities were chosen. 120 questionnaire were distributed and direct observation were conducted in order to evaluate the phenomenon. Findings revealed that physical elements in the street do affect safety perception.